Cultural Heritage and the Literary Archive : Objects, Institutions, and Practices between the Analogue and the Digital - Sommer, Tim (New York : Routledge, 2025)
Modern literary archives play a key role in how authors' lives and works get canonized and consecrated as cultural heritage. This interdisciplinary volume combines literary studies, book history, textual criticism, heritage studies, archival theory, and the digital humanities to examine the past, present, and future of literary archiving. Featuring contributions from leading international scholars and archive professionals, the book explores the objects, practices, and institutions that have been at the heart of the modern archival landscape since its emergence in the nineteenth century. Covering a wide range of questions, the volume reconstructs how literary manuscripts turned into secular relics and analyzes the impact that the rise of the archive has had on the scholarly study and public perception of literature as cultural heritage. Individual chapters range from historical accounts of the Romantic origins of manuscript worship to critical discussions of the archiving of contemporary writers' born-digital material.
List of ContributorsAcknowledgementsIntroduction: Literature, Heritage, ArchiveTim SommerPart I: Historical Origins1. "This Warm Scribe, My [Profitable] Hand": Agency and the Acquisition of Literary ArchivesChristopher Fletcher2. British Romantic Poetry and/as Cultural Heritage: Lord Byron, Percy Bysshe Shelley, Mary RobinsonTim Sommer3. Women Writers and Publisher Archives: Jane Austen and BeyondMichelle LevyPart II: Institutional Collecting4. The Collections Cycle of the Modernist Archive MarketAmy Hildreth Chen5. "Operation Manuscript": A National Institutional Response to Collecting Contemporary Literary HeritageJamie Andrews6. Manuscript in the Writer's House MuseumNicola J. WatsonPart III: Authors and Archives7. Archival Anxieties: On Memory and ForgetfulnessStephen Enniss8. Archives as Texts and the Stories They TellJennifer Douglas9. Writers' Libraries and Vestigial Notes as Cultural Heritage: Minding the Gaps in the Material RecordDirk Van HullePart IV: Digital Archives, Digital Heritage10. Capturing, Collaborating, and Curating: A Community-Led Approach to Contemporary Born-Digital Literary ArchivesJustine Mann11. Invisible Touches: The Challenge of the Hidden Revolution in Bookmaking for Publishers' ArchivesMatthew G. KirschenbaumIndex
Keywords: Cultural property; Cultural property -- Protection; LITERARY CRITICISM / Books & Reading; HISTORY / Modern / General; LITERARY CRITICISM / General